Study of morphological patterns of dermatophytosis - R., Harshini Aishwarya; Jacob, Sheba M.; Sharada, R. G. (International Journal of Research in Dermatology, 2022)
Background: Dermatophytosis (tinea) refers to the superficial mycosis of keratinized tissues like hair, skin or nail caused by dermatophytes. It is a problem of significant importance because of the increasing trend in the number of cases that are unresponsive to treatment and presenting with recurrence. Methods: 148 patients with dermatophytosis attending the outpatient department of dermatology were enrolled based on inclusion and exclusion criteria during the 3-month time period between April 2021 and June 2021. Results: Out of the 148 cases, 93 (62.83%) were males and 55 (37.16%) were females. Highest number of cases were seen in the age group 21–30 with 61 (41.21%) cases. Among the 148 cases, 139 (93.91%) cases presented with dermatophytosis at a single site while 9 (6.09%) cases had multiple sites of dermatophytosis. Out of the 139 cases who had dermatophytosis at a single site, 77 cases (55.39%) were found to have corporis pattern. Conclusions: The most common pattern of dermatophytosis found was the annular pattern and young males were the most commonly affected population.